Improving crop production for food security and improved livelihoods on the East India Plateau II. Crop options, alternative cropping systems and capacity building. (July 2015) - Cornish, Peter S.; Choudhury, Avijit; Kumar, Ashok; Das, Sudipta; Kumbakhar, Kuntalika; Norrish, Shane; Kumar, Shivendra
Highlights: Smallholders successfully grew rainfed rice by direct-seeding with no puddling. Vegetables were adopted in the kharif, a new pre-kharif season, and the rabi (with irrigation). Mustard and wheat proved feasible with minimal irrigation, or rainfed after short-duration rice. Rapid transition from rice-fallow to intensive systems attributed to adult-learning approach. Good socio-economic benefits were documented. Abstract: Rainfed transplanted rice ( Oryza sativa ) is the staple crop of the East India Plateau, with >80% grown in a rice-fallow on terraced and bunded hill-slopes ('medium-upland') where it is low yielding and drought-prone despite high rainfall (>1200 mm). Paper I attributed this to inadequate ponding for transplanted rice whilst identifying the potential for risk-free alternative kharif (monsoon period) crops, including direct-seeded rice grown without ponding ('aerobic' rice), and for second-cropping with little or no irrigation. Paper II reports research with Tribal smallholders in Purulia District, West Bengal that aimed to evaluate these cropping options using a participatory process that further aimed to 'improve the situation' of participating families. The feasibility of short-duration aerobic rice was confirmed experimentally in 2007 and 2008 and in wider adoption by farmers in 2010 when conventional rice could not be transplanted. Best yields in each year were >4 t ha −1 . Mustard ( Brassica juncea ) and wheat ( Triticum aestivum ) planted after medium-duration rice yielded up to 0.95 t ha −1 and 2.6 t ha −1 with one irrigation of 40–50 mm for establishment; but modelling suggests there is enough residual soil water after short-duration (early-maturing) rice to exceed these yields in most years, even without irrigation. Significant P-fertiliser was required with these crops to correct acute deficiency. Rainfed vegetables were grown in the kharif and then adapted by farmers to pre- kharif cropping, and to the rabi (winter) if they had some access to irrigation. Monitoring land-use revealed rapid, sustained adoption of more diverse and intensive cropping, with significant social and economic benefits. We attributed adoption to the participatory process used, that strengthened farmer's capacity to innovate. The systems implemented by farmers needed no expenditure on new water resources, suggesting that comprehensive watershed development (WSD) is not a prerequisite to replacing the rigid rice-fallow with safer climate-responsive systems, although investment in small water harvesting structures may be needed for rabi vegetable crops. The technology evaluated, plus the process of intervention that built capacity, together provide a foundation for wider adoption of less risky cropping systems with greater water productivity.